Space, Time and Language in Plutarch - Geōrgiadu, Aristula; Oikonomopulu, Aikaterinē (2017)
'Space and time' have been key concepts of investigation in the humanities in recent years. In the field of Classics in particular, they have led to the fresh appraisal of genres such as epic, historiography, the novel and biography, by enabling a close f...